Children's experiences of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME): a systematic review and meta-ethnography of qualitative studies. Issue 1 (13th January 2017) - Parslow, Roxanne M; Harris, Sarah; Broughton, Jessica; Alattas, Adla; Crawley, Esther; Haywood, Kirstie; Shaw, Alison
Abstract : Objective: To synthesis the qualitative studies of children's experiences of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME). Design: Systematic review and meta-ethnography. Background: CFS/ME is an important disabling illness, with uncertain cause and prognosis. As a result, children with CFS/ME can find themselves living with greater uncertainty and stigma, exacerbating the impact of the condition. There is a growing body of qualitative research in CFS/ME, yet there has been no attempt to systematically synthesis the studies involving children. Methods: Studies exploring the experiences of children diagnosed with CFS/ME, published or unpublished, using qualitative methods were eligible. MEDLINE, EMBASE, PsycINFO and CINAHL databases were searched as well as grey literature, reference lists and contacting authors. Quality assessment was done independently using the Critical Appraisal Skills Programme (CASP) checklist. Studies were synthesised using techniques of meta-ethnography. Results: Ten studies involving 82 children with CFS/ME aged 8–18 were included. Our synthesis describes four third-order constructs within children's experiences: (1) disruption and loss: physical, social and the self; (2) barriers to coping: suspension in uncertainty, problems with diagnosis and disbelief; (3) facilitators to coping: reducing uncertainty, credible illness narratives, diagnosis and supportive relationships and (4) hope, personal growth and recovery. CFS/ME introduces profound biographical disruption through its effects on children's ability to socialise, perform school and therefore how they see their future. Unfamiliarity of the condition, problems with diagnosis and felt stigma prevent children from forming a new illness identity. Children adopt coping strategies such as building credible explanations for their illness. Conclusions: Physical, social, emotional and self-dimensions of life should be included when treating and measuring outcomes from healthcare in paediatric CFS/ME. There is a need for greater recognition and diagnosis of childhood CFS/ME, specialist advice on activity management and improved communication between health and education providers to help children cope with their condition.